2014
DOI: 10.1007/s00021-014-0182-5
|View full text |Cite
|
Sign up to set email alerts
|

A Weak-L p Prodi–Serrin Type Regularity Criterion for the Navier–Stokes Equations

Abstract: We give simple proofs that a weak solution u of the Navier-Stokes equations with H 1 initial data remains strong on the time interval [0, T ] if it satisfies the Prodi-Serrin type condition u ∈ L s (0, T ; L r,∞ (Ω)) or if its L s,∞ (0, T ; L r,∞ (Ω)) norm is sufficiently small, where 3 < r ≤ ∞ and (3/r) + (2/s) = 1.Mathematics Subject Classification. 35Q30, 76D03, 76D05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…Note that thanks to (9), (10) is a weaker assumption than (5) as it is implied by the latter. The affirmative answer to this conjecture was established in [2], [7] and later refined in many follow-up papers, including [1], [3], [9], [13], [16], [17], [19], [27], [28], [30]. Roughly speaking, most of the aforementioned improvements of (5) [31] it is shown that u is smooth as long as…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Note that thanks to (9), (10) is a weaker assumption than (5) as it is implied by the latter. The affirmative answer to this conjecture was established in [2], [7] and later refined in many follow-up papers, including [1], [3], [9], [13], [16], [17], [19], [27], [28], [30]. Roughly speaking, most of the aforementioned improvements of (5) [31] it is shown that u is smooth as long as…”
Section: Introductionmentioning
confidence: 91%
“…Many generalizations and refinements of (5) have been proved, see e.g. [3], [5], [8], [12], [31], [34]. Mathematically the pressure p serves as the Lagrange multiplier of the incompressibility constraint divu = 0.…”
Section: Introductionmentioning
confidence: 99%
“…However the achievement of this goal is still out of the question. In particular, there is still no satisfactory answer to the question of well-posedness of the Cauchy problem of (1)- (3).…”
Section: Introductionmentioning
confidence: 99%
“…On could further show that such a smooth Leray-Hopf solution must be the unique solution to (1)- (3). Therefore the well-posedness problem would be settled if all Leray-Hopf solutions could be shown to be smooth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation